Membangun Generasi Z Humanis: Pendekatan Internalisasi Nilai Agama dalam Keterampilan Digital - Sodikin, Sodikin; Siswati, Vialinda (Kartika: Jurnal Studi Keislaman, 2024)
The growing moral degradation in cyberspace, with its various negative behaviors, has caused unrest. This qualitative study aims to obtain a detailed picture of the internalization of religious values ​​in digital skills so that the existence of cyberspace is more humane and does not degrade human dignity. The informants in this research are Dalwa TV employees who actively present positive information in presenting digital information. The results of this research show that to build a humanist Generation Z through internalizing religious values ​​in digital skills is to know the characteristics and relationship of Gen Z with the digital world, the urgency and effect of religious values ​​in shaping ethical behavior and decision-making in the digital context, and strategies. Integrated internalization of religious values ​​in Generation Z. This strategy includes (1) introducing religious principles in education, (2) Integration religious teachings into digital literacy programs, and (3) Fostering a culture of empathy and compassion through religious values. This research confirms that Islamic boarding schools play a major role in building a humanist Generation Z through an approach to internalizing religious values ​​in developing digital skills. Future researchers can conduct comparative studies in Islamic boarding schools that focus on understanding the impact of online interactions on mental health and well-being.